Lifetime Prevalence of Verbal, Physical, and Sexual Abuses in Young Elite Athletics Athletes - Bermon, Stéphane; Adami, Paolo Emilio; Dahlström, Örjan; Fagher, Kristina; Hautala, Janna; Ek, Anna; Anderson, Christer; Jacobsson, Jenny; Svedin, Carl Göran; Timpka, Toomas (Frontiers in Sports and Active Living, 2021)
To examine prevalence of verbal, physical and sexual abuses in young elite athletes, a cross sectional questionnaire-based survey was conducted during the World Athletics under 20 World Championships. This questionnaire aimed at distinguishing between abuses perpetrated in the context of Athletics from those which were unrelated to Athletics. Four hundred and eighty athletes (52.3%, male) from North America, South America, Europe, Africa, Asia, and Oceania took part in the electronic anonymous survey. Outside Athletics setting, no gender difference was found for the prevalence of verbal, physical and sexual abuses. However, 45 males (18% of the male population) and 34 females (15% of the female population) athletes reported sexual abuse. Asian athletes reported a slightly higher rate of sexual abuse; three quarters of them being non-touching abuses. Inside Athletics setting, no gender difference was found for the prevalence of verbal, physical and non-touching sexual abuses. However, 58 males (23%) and 47 females (21%) reported verbal abuses. 31 males (12%) and 20 females (9%) reported physical abuses, whereas 30 males (12%) and 17 females (7%) reported sexual abuses. Physical abuses were slightly more frequent in Asia and in Africa and less frequent in South America. Sexual abuses inside Athletics also differed over regions, and were unexpectedly twice more frequent than expected in Asia and slightly less frequent than expected in Europe. Friends and partners were identified as the more frequent (>50%) abusers outside or inside the athletics settings, whereas outside athletics and inside athletics, coaches were identified as sexual abuse perpetrators in 8% and 25% of cases, respectively. The prevalence of verbal, physical or sexual abuses is high but consistent with what has been reported in United Kingdom, Norway, Canada, and Sweden at national level in recreational or elite athletes. Sexual abuse, including touching or penetrative abuses, occurred significantly more often in male athletes when compared to female athletes. This finding invites healthcare and social workers, and policymakers to also consider the risk of sexual abuse of young male athletes in Athletics. These results also call for longitudinal studies on young elite athletes.